Smart auction system flow model for Agro-Based sector farmers using blockchain technology. (2023) - Sivalakshmi, P; Shanthi, K.G; Sangeethalakshmi, K; SeshaVidhya, S; Sandhiya, G; Rajkumar, M
Abstract: Blockchain technology has wide area of application, this article is very particular on emphasising another important field of application named Agro-products supply chain. Wherein this era, and the future needs to nurture the agriculture sector along with latest technologies, so that nation would make a revolution in the process of food supply from the farm to the plate. The main drawback in the agriculture supply chain is lack of transparency in food production and distribution, costly middleman, limited financial resources & disconnection between supplier and retailer. So this article proposes, suitable theoretical auction flow model to overcome all the issues highlighted in this agro-sector, we would like to give the solution by improving the transparency in the supply chain, by providing farmers direct access to suppliers through an appropriate auction system with an option of immediate payment on delivery & transparent transaction information to them. Further we can involve government as a central authority to overcome the technical aspects, education, policies and regulatory frame works, in turn they can generate job opportunities to the unemployed graduates.